Membangun Sekolah Bebas Bullying - Arum, Siti Khumairoh Kusuma; Aslam, Ananda; Kurnia Hadi, Adi Moh.; Hidayat, Nashiffa Thuraya; Hanafiah, Yuliana; Astuti, Rahayu; Affani Sidqi, Mochamad; Winanto, Wahyu Andika; Salsabila, Annisa Shafa; Aditriansyah, Muhammad Yoga; Saputra, Elton Krisna; Elthaufani, Lucky; Jadidah, Fikrotul (CV. Era Digital Nusantara, 2025)
KKN activities at Pratiwi Junior High School on May 14, 2024, aim to expand the knowledge and understanding of Pratiwi Junior High School students and increase awareness among students to prevent bullying, so as to